The Role of Organizational Communication to Resolve Conflicts in the Internal Organization Environment of HMJ MPI FITK UINSU - Tamimi Mujahid; Salsabila Erliani; Rizki Akmalia; Nurul Anjani Daulay; Zahra Jannah; Malik Ubaidillah (Pusdikra-Publishing.com, 2023)
For an organization, conflict is a natural part of an activity and cooperation carried out within and among members or components of the organization in order to realize organizational goals. Conflict is a natural thing, but it still needs what is called good, planned, and structured conflict management so that conflict does not become the beginning of the destruction of an educational institution. So it is necessary to discuss about